Hypoxic transcriptional phenotype and cellular ultrastructural changes of tumor-associated macrophages in gliomas - FAN Haizhen; FAN Haizhen; WANG Lixia; CHENG Yue (陆军军医大学学报)
‍Objective‍　‍To investigate the effects of hypoxia on the transcriptional phenotype and ultrastructure of tumor-associated macrophages (TAMs) in glioma. Methods‍　‍CD14+ monocytes were isolated from healthy human peripheral blood samples collected from the Blood Bank of the First Affiliated Hospital of Army Medical University, and the cells were induced to differentiate into TAMs through co-culture with glioma cell-conditioned medium. Hypoxic TAM models were established using varying concentrations of cobalt chloride hexahydrate (CoCl2, 50~400 μmol/L) or hypoxic conditions (1%, 5%, 10%O2) for 48 h, while normoxic TAM models (21%O2) served as controls. RT-qPCR and transcriptome sequencing were employed to analyze transcriptional changes in TAMs under normoxic and hypoxic conditions. Gene set enrichment analysis (GSEA) was applied to compare the differences in angiogenesis, glycolysis and other hypoxia-responsive pathways between the 2 conditions. Transmission electron microscopy (TEM) or immunofluorescence staining was conducted to assess the ultrastructural alterations in cytoskeleton, endoplasmic reticulum (ER), and mitochondria in normoxic and hypoxic TAMs (1%O2). Results‍　‍Hypoxic TAMs exhibited up-regulated transcription of hypoxia-responsive markers (oxygen transport, glycolysis, pro-angiogenesis), with the effects correlating with hypoxia severity（P<0.05）. GSEA revealed significant up-regulation of hypoxia, angiogenesis regulation, glycolysis and gluconeogenesis, and starvation stress pathways, alongside down-regulation of innate immunity, macrophage activation, cytoskeleton, and protein maturation pathways in hypoxic TAMs (P<0.05). TEM and immunofluorescence staining demonstrated obvious ultrastructure changes, including disrupted cytoskeletal organization, shortened rough ER with reduced ribosomes, mitochondrial swelling with cristae damage, and diminished ER-mitochondria contacts in hypoxic TAMs. Conclusion‍　‍CoCl2 and hypoxia induce a hypoxic transcriptional phenotype in TAMs, which may potentially associated with ultrastructural remodeling of the cytoskeleton, ER, and mitochondria.